2022
DOI: 10.1111/jfpe.14053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic pretreatment on drying kinetics and physio‐mechanical characteristics of peach slices

Abstract: Peach, which is one of the most critical garden products in Iran has a lot of postharvest lesions. In this sense, processing the product would result in reducing the postharvest lesions. Recently, ultrasound waves have been widely applied as a new pretreatment method in drying food. Herein, we aim at investigating the effect of high power ultrasound pretreatment on the drying kinetics of peach slices. The effective moisture penetration coefficient, color changes and elastic modulus were investigated. The dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…These results indicate that the Page equation is a suitable to model in describing the OD procedure of apple slices under the various sonication power levels and osmotic solution concentrations. The influence of ultrasonic pre-treatment on drying kinetics and physio-mechanical properties of peach slices was examined and modeled by Akhoundzadeh Yamchi et al 26 . According to the results, applying sonication before drying decreases the drying duration about 40%.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the Page equation is a suitable to model in describing the OD procedure of apple slices under the various sonication power levels and osmotic solution concentrations. The influence of ultrasonic pre-treatment on drying kinetics and physio-mechanical properties of peach slices was examined and modeled by Akhoundzadeh Yamchi et al 26 . According to the results, applying sonication before drying decreases the drying duration about 40%.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a 40% reduction in drying time for ultrasound treated peach slices was reported. 30 Reductions in drying time of 19% and 14.3% were also recorded for ultrasound pretreated dried pineapple slices with an ultrasound time of 20 and 30 min, respectively. 31 A series of mechanisms are responsible for these changes in biological material as a result of ultrasound pretreatment.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, this model was chosen to describe, and predict the drying behavior of bitter melon with the help of infrared under temperature, distance from infrared lamps, and ultrasound pretreatment in different periods. Akhoundzadeh Yamchi et al (2023), Du et al (2023), Zang et al (2023), and Polat et al (2022) reported the Midilli model as an appropriate model to describe the drying demeanor of apricot, paddy, and sweet potatoes in an infrared dryer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This system can work continuously, and pulsed, has digital power control from 0% to 100%, and has two temperature sensors inside, and outside. In order to examine the impact of the infrared dryer and ultrasound waves, bitter melon at three temperature of 50, 60, and 70°C, at three distances of 10, 15, and 20 cm from infrared lamps, and ultrasound treatment at 10, and 20 min with a power of 20%, and in three repetitions until the samples reached more stable equilibrium moisture, It was done (Akhoundzadeh Yamchi et al, 2019). Schematic diagram of infrared drying of bitter melon under different ultrasonic is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation